2003
DOI: 10.1046/j.0366-077x.2003.05632.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis by Toll-like receptor-7 agonist in tissue cultures

Abstract: Toll-like receptor (TLR)-7 agonists represent a new group of immune response modifiers, which include imiquimod and resiquimod (R-848). Topically applied imiquimod is used for the treatment of both external and perianal genital warts, and benign and malignant epithelial lesions. Based on the induction of interferons and other cytokines in vitro and in vivo, regression of epithelial lesions probably depends on induction of both innate and cellular immune responses. As clinical remission is not always associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 17 publications
(17 reference statements)
7
52
0
4
Order By: Relevance
“…However, imiquimod exerts an additional direct proapoptotic activity against tumor cells (Scho¨n et al, 2003), a surprising observation that was confirmed in vivo in tumors of different origin (Sidbury et al, 2003;Sullivan et al, 2003;Scho¨n et al, 2004;Vidal et al, 2004) as well as on the cellular level in vitro (Meyer et al, 2003). While the proapoptotic activity of imiquimod is independent of membrane-bound death receptors, shifts of Bcl-2 proteins in favor of the proapoptotic Bax were observed.…”
Section: Proapoptotic Activity Of Imiquimodmentioning
confidence: 95%
“…However, imiquimod exerts an additional direct proapoptotic activity against tumor cells (Scho¨n et al, 2003), a surprising observation that was confirmed in vivo in tumors of different origin (Sidbury et al, 2003;Sullivan et al, 2003;Scho¨n et al, 2004;Vidal et al, 2004) as well as on the cellular level in vitro (Meyer et al, 2003). While the proapoptotic activity of imiquimod is independent of membrane-bound death receptors, shifts of Bcl-2 proteins in favor of the proapoptotic Bax were observed.…”
Section: Proapoptotic Activity Of Imiquimodmentioning
confidence: 95%
“…It was shown in vitro that imiquimod can directly induce apoptosis of tumor cells using several skin and bladder cancer cells lines, as well as tumor tissue cultures [97][98][99][100][101]. For the skin cancer cell lines, it was demonstrated that this proapoptotic activity was independent of membrane-bound death receptors.…”
Section: Tumor Cellsmentioning
confidence: 99%
“…It was reported that imiquimod induced apoptosis of human epithelial cells, keratinocytes, and mouse Wbroblasts [8,15]. Topical application of imiquimod cream to keloids alters expression of genes associated with apoptosis including caspase-3 [9].…”
Section: Introductionmentioning
confidence: 99%